Entering the molecular era of gastrointestinal oncology: current updates and challenges - Wang-Gillam, Andrea; Lim, Kian-Huat (Journal of Gastrointestinal Oncology; Vol 8, No 3 (June 23, 2017): Journal of Gastrointestinal Oncology (Novel Biologics In Era of Precision Medicine)1, 2017)
Cancer diagnosis and treatment drastically improved during the molecular era. The past four decades of intense research have unveiled key dysregulated genetic or signaling events that drive specific cancer types. As such, biologics as a class of therapeutic agents that target these critical signaling events, have become a major focus in the development of anti-cancer drugs.